Women in the Czech Countryside Through The View of Land Registers - Klvaňová, Daniela (My University, 2024)
This article is an attempt to present land registers as a source through which we can look not only at the history of the rural population at overal, but also at the history of (rural) women. Some possibilities of using this source are demonstrated by the example of two Czech land registers kept for the village of Bělá. The data obtained present women in different roles and give insight into the fates and life strategies of the serf population.
Ženy na české vsi očima pozemkových knih
Keywords: women; serfdom; Czech countryside; land registers; 18th century; 19th century, household; ženy; poddanství; česká vesnice; pozemkové knihy; 18. století; 19. století; domácnost